Liver transplantation for hepatocellular carcinoma after successful treatment of macrovascular invasion – a multi‐center retrospective cohort study. (20th February 2020) - Assalino, Michela; Terraz, Sylvain; Grat, Michal; Lai, Quirino; Vachharajani, Neeta; Gringeri, Enrico; Bongini, Marco Angelo; Kulik, Laura; Tabrizian, Parissa; Agopian, Vatche; Mehta, Neil; Brustia, Raffaele; et al.
Summary: Macrovascular invasion is considered a contraindication to liver transplantation for hepatocellular carcinoma (HCC) due to a high risk of recurrence. The aim of the present multicenter study was to explore the outcome of HCC patients transplanted after a complete radiological regression of the vascular invasion by locoregional therapies and define sub‐groups with better outcomes. Medical records of 45 patients were retrospectively reviewed, and imaging was centrally assessed by an expert liver radiologist. In the 30 patients with validated diagnosis of macrovascular invasion, overall survival was 60% at 5 years. Pretransplant alpha‐fetoprotein (AFP) value was significantly different between patients with and without recurrence ( P = 0.019), and the optimal AFP cutoff was 10ng/ml (area under curve = 0.78). Recurrence rate was 11% in patients with pretransplant AFP < 10ng/ml. The number of viable nodules ( P = 0.008), the presence of residual HCC ( P = 0.036), and satellite nodules ( P = 0.001) on the explant were also significantly different between patients with and without recurrence. Selected HCC patients with radiological signs of vascular invasion could be considered for transplantation, provided that they previously underwent successful treatment of the macrovascular invasion resulting in a pretransplant AFP < 10 ng/ml. Their expected risk of post‐transplant HCC recurrence is 11%, and further prospective validation is needed.